The effect of hypnobirthing relaxation on the scale Pain in labor during the active phase I: Hypnobirthing Relaxation - Debby Pratiwi; Dalimawaty Kadir; Julina Br Sembiring (Science Midwifery, 2023)
The hypnosis method can be carried out from pregnancy to delivery, it can help reduce anxiety and fear levels. Hypnosis techniques can help relax the muscles so that the mother avoids anxiety and can help the mother be more calm in facing labor. Objective: This study was to determine the effect of implementing hypnobirthing on reducing pain during labor at the Wanti Midwife Clinic in Medan in 2022. Methods: This study used a quasi-experimental method with one group pretest and post test without control design. The population is 15 mothers giving birth in September 2022. Data analysis uses univariate and bivariate analysis with paired match pair tests. Results: The results showed that of the 15 respondents, before being given hypnobirthing the majority of respondents experienced severe pain 6 people (40.0%) and the minority reduced unbearable pain 9 people (60.0%). after being given hypnobirthing the majority of respondents experienced moderate pain 14 people (93.3%) and a minority experienced severe pain 1 respondent (6.7%). The average pain before being given hypnobirthing was 2.60. The average pain after being given hypnobirthing was 1.07 with a ρ-value of 0.000 (<0.05). Conclusion: The conclusion shows that there is an effect of reducing pain before and after hypnobirthing is carried out for mothers giving birth at the Wanti Midwife Clinic. It is recommended that health workers improve their skills (participate in training and seminars) in efforts to assist childbirth using the hypnobirthing method.